The Impact of Full Practice Authority for Nurse Practitioners and Other Advanced Practice Registered Nurses in Ohio - Martsolf, Grant R. (RAND Corporation, 2015)
RAND Corporation researchers identified three high-quality studies addressing the effect that scope-of-practice (SOP) laws can have on health-care access, quality, and costs and describe the potential effect of removing SOP restrictions for advanced practice registered nurses in the state of Ohio.